Informação e Sociedade: Estudos Vol. 23, n. 3 (2013) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Informação e Sociedade: Estudos Vol. 23, n. 3 (2013)Link de acesso ao númerohttp://www.ies.ufpb.br/ojs2/index.php/ies/issue/view/1272/showToc